2014
DOI: 10.5433/1679-0359.2014v35n1p67
|View full text |Cite
|
Sign up to set email alerts
|

Influência do 24-epibrassinolídeo na tolerância ao estresse salino em plântulas de arroz

Abstract: Salinity can be considered a limiting factor to the growth and development of plants to affect various physiological processes. The aim of this study was to determine the effect of 24 -epibrassinolide in emergence, seedling growth, leaf area and chlorophyll concentration in two cultivars of rice in salt stress condition. The study was conducted at the research laboratory of seeds and greenhouse of the Department of Botany UFPel. Rice seeds of cvs. BRS Bojurú tolerant to salinity and BRS Querência not tolerant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
5
0
7
Order By: Relevance
“…When the plants were irrigated with 3.8 dS m -1 water, the data fitted to the regression model as K doses increased and, from the dose of 71% (0.699 mg g -1 FM), plants irrigated with water of highest electrical conductivity showed a sharp reduction in the chlorophyll b contents. According to Larré et al (2014), the enzyme chlorophyllase is stimulated in the first days of exposure to stress (moderate stress), but this activity is strongly inhibited by high salt concentration. Nevertheless, it can be inferred that K fertilization positively influences chlorophyll index, if adequate amount is provided, because besides increasing N assimilation and transport, K is responsible for the movement of the stomatal guard cells, regulating the entry of CO 2 , which serves as fuel for photosynthesis, as reported by Appezzato-da-Glória & Carmello-Guerreiro (2012 increased and, according to the regression equation ( Figure 4B), there was an increment of 7.56% for every 25% increase in K doses.…”
Section: Results and Discussonmentioning
confidence: 99%
“…When the plants were irrigated with 3.8 dS m -1 water, the data fitted to the regression model as K doses increased and, from the dose of 71% (0.699 mg g -1 FM), plants irrigated with water of highest electrical conductivity showed a sharp reduction in the chlorophyll b contents. According to Larré et al (2014), the enzyme chlorophyllase is stimulated in the first days of exposure to stress (moderate stress), but this activity is strongly inhibited by high salt concentration. Nevertheless, it can be inferred that K fertilization positively influences chlorophyll index, if adequate amount is provided, because besides increasing N assimilation and transport, K is responsible for the movement of the stomatal guard cells, regulating the entry of CO 2 , which serves as fuel for photosynthesis, as reported by Appezzato-da-Glória & Carmello-Guerreiro (2012 increased and, according to the regression equation ( Figure 4B), there was an increment of 7.56% for every 25% increase in K doses.…”
Section: Results and Discussonmentioning
confidence: 99%
“…A reduction in dry mass can also reflect the metabolic cost of energy, associated with adaption to salinity and reductions in carbon gain (Richardson and McCree, 1985;Larré et al, 2014).…”
Section: Initial Developmentmentioning
confidence: 99%
“…Similarly, for fresh shoot weight (p = 0.002) and free root weight (p = 0.01) and dry shoot weight (p = 0.02) and dry root weight (p = 0.005), plants cultivated using the highest Cu concentration showed 19, 46, 24, and 40%, respectively, of the values observed for the control plants. These results show that the strategy of plants under stress due to high metal concentrations is to use tolerance mechanisms, limiting other processes such as growth (POSMYK et al, 2009;LARRÉ et al, 2014). Furthermore, recent studies have shown a relationship between the biochemical phase of photosynthesis, which is highly sensitive to the effects of heavy metals, and the decrease in growth (SHI-SHENG, 2007).…”
Section: Resultsmentioning
confidence: 94%